Influence of Particle Size and Soaking Conditions on Rheology and Microstructure of Amorphous Calcium Polyphosphate Hydrogel. Issue 12 (7th August 2015) - Song, Wei; Seta, Joseph; Kast, Rachel E.; Auner, Gregory W.; Chen, Liang; Markel, David C.; Ren, Weiping
Abstract : Amorphous calcium polyphosphate (ACPP), an inorganic polymer ceramic, has shown promise as a drug delivery matrix following a repeat gelling protocol. This study described a simple method of preparing ACPP hydrogel in the presence of an excess volume of water. The increased water availability accelerates water molecule ingress and microstructural transformation of ACPP hydrogels. The impact of some experimental settings (soaking time, temperature, stirring, and ACPP particle size) on the physiochemical and rheological natures of ACPP hydrogel were investigated and from which possible hydrogel formation mechanisms were inferred. We believe that the formation of ACPP hydrogel is through the mechanisms of intermolecular ionic interaction and entanglement of polyphosphate chains. The potential application of ACPP hydrogel as a ceramic matrix for sustained drug release warrants further investigation.